A three-dimensional coupled thermo-hydro-mechanical numerical model with partially bridging multi-stage contact fractures in horizontal-well enhanced geothermal system. (July 2021) - Yu, Pengliang; Dempsey, David; Archer, Rosalind
Abstract: Enhanced Geothermal Systems (EGS), engineered deep rock heat exchangers, are often touted for their massive untapped renewable energy potential. However, numerous technical and financial challenges must be overcome before the technology is widely deployed. To be viable, EGS must engineer a heat sweep by circulating fluid through a large volume of rock while minimizing fast pathways that create thermal short circuits. Here, we propose a new horizontal EGS well design with partially bridging multi-stage hydraulic fractures (Fig. 1b) to improve heat extraction from hot dry rock (HDR). In order to increase fluid circulation through the stimulated reservoir volume (SRV) between fractures, the hydraulic fractures are created in an alternating pattern between injection and production wells, with each stopping short of connecting the second well. To test this design, we developed a thermal-hydro-mechanical (THM) coupling model and investigated heat extraction performance and reservoir stress evolution during operation. Fractures were modelled as opening contact surfaces with system stresses evolving according to thermal, poroelastic, and fracture opening effects. Based on the model, the temperature performance of proposed EGS design model is compared with the commonly used fully bridging EGS design model (Fig. 1a). An investigation of thermal performance showed that the proposed design obtains higher production temperatures and delays thermal breakthrough by several years compared to a fully-bridging fracture design. It also results in a greater degree of secondary stimulation of the SRV as cold fluids are forced further into the rock matrix. These results indicate that the partially-bridging fracture design is a promising candidate for practical EGS implementation. Highlights: A novel partially bridging horizontal EGS well design model is proposed. Multistage fractures are modelled as opening contact surfaces. A 3D THM coupling model with system stress evolving according to thermal, poroelastic, fracture opening effects is presented. Heat extraction performance, reservoir stress evolution of the proposed design are compared with fully bridging design model. The separate role of thermoelastic, poroelastic, fracture opening effects in EGS reservoir stress evolution are discussed.